The lawyer's guide to writing well - Goldstein, Tom; Lieberman, Jethro K. (Jethro Koller) (University of California Press, 2016)
This best-selling book outlines the causes and consequences of bad legal writing and prescribes straightforward, easy-to-apply remedies that will make your writing readable. Usage notes address lawyers' most common errors, and editing exercises allow readers to test their skills, making this an invaluable tool for practicing lawyers as well as a sensible grounding for law students. New sections in this edition: - Getting to the point - Communicating digitally - Writing persuasively - Twenty-five common mistakes"--Provided by publisher